Sleep Quality, Decision Making and Psychological Well-being among Auto-Drivers - Noor, Mamoona; Ahmad, Gulzar (Journal of Pakistan Psychiatric Society, 2021)
ObjectiveThe present study aims to investigate the effect of sleep quality on decision making and psychological well-being of auto drivers and to find out the relationship between these variables.Study DesignCorrelational design was used in the study.Place and Duration of the Study The study was conducted within six months in Lahore.Subjects and MethodsThree hundred auto drivers were undertaken in this study and convenient sampling was used for the collection of data. Pittsburgh Sleep Quality Index (Dr. Daniel J. Buysse, 1989), Psychological Well-being Scale (Dr. Carol Ryff, 1998) and Decision-Making Questionnaire (David French, 1993) and demographic questionnaire were used to assess the variables of study.ResultsCorrelational analysis indicated that decision making is negatively correlated with poor sleep quality while it is positively correlated with psychological well-being, while poor sleep quality is significantly negatively correlated with psychological well-being.Conclusion This study concludes that poor sleep quality decreases the level of decision making and psychological well-being of auto-drivers. The present findings of study are important for auto drivers as it will help them to avoid road or traffic accidents that occur because of poor decision making capacity and psychological well-being and these are mainly related with poor sleep quality.